NITROGEN FERTILIZATION OF RICE, COMMON BEAN AND CORN WITH ENHANCED-EFFICIENCY FERTILIZER - Reis Jr, Roberto dos Anjos; Cobucci, TarcÃcio; Sonego, Darci (REVISTA DE AGRICULTURA, 2019)
Nitrogen (N), a mineral element required in greater quantity by plants, has a low efficiency use in agriculture, resulting in economic and environmental problems. N enhanced efficiency fertilizers use is one of the strategies to increase N fertilization efficiency. Polymer urea coating has been used to produce enhanced efficiency fertilizers. However, there are a lot of polymers for this type of coating, which may lead to divergence of results. Validation of this technology to guarantee its viability in agriculture is necessary. This study aimed to evaluate rice, common bean and corn morphological characteristics, foliar N contents and yields and N fertilization efficiency in response to N rates and sources. Field experiments were carried out on these crops, comparing N fertilizers performance. Each experiment was formed by a factorial design comparing N sources (urea and Policote coated urea) and rates, besides Control. N fertilization influenced rice, common bean and corn morphological characteristics, foliar N contents, yields and N fertilization efficiency. Increasing N rates increased rice, common bean and corn morphological characteristics and yields. Policote coated urea showed higher agronomic efficiency of nitrogen fertilization and higher yields than urea in rice, common beans and corn crops.